Особенности состава углекислых минеральных вод природного комплекса Чойган - Копылова Ю. Г. Юлия Григорьевна; Аракчаа К. Д.; Гусева Н. В. Наталья Владимировна; Рычкова К. М.; Хващевская А. А. Альбина Анатольевна; Шестакова А. В. Анастасия Викторовна; Оргильянов А. А.; Крюкова И. Г.; Бадминов П. С.; Данилова М. А. (2015, 2015)
В фонде НТБ ТПУ отсутствует